Peluang ekonomi budidaya udang Windu petani tambak kawasan pesisir utara Brebes - Hartanti, Ninik Umi; Suyono, Suyono; Cahyani, Alinda; Dina, Karina Farkha (Nur Science Institute, 2024)
This research aims to identify problems and opportunities for economic development in tiger prawn cultivation, which is an important part of implementing pilot program activities to accelerate the dissemination of cultivation technology innovation in the Brebes Regency and its surroundings. The method used in this research is Participatory Rural Appraisal (PRA) with techniques for collecting information and recognizing community needs through questionnaires. The research results showed that 91.7% of respondents in 3 Brebes sub-districts had shrimp cultivator groups. The activity of the shrimp cultivator group in this study was 83.3%, indicating that the cultivator group was running. In terms of the area of pond land for cultivators, more than 66.7% of pond cultivators have land with an area of more than 50 Ha. Regarding the infrastructure factor around the pond, respondents answered that 58.3% of respondents answered that infrastructure allows for the success of tiger prawn cultivation. Regarding the ease of marketing factor, 83.3% of respondents answered that marketing was easy. Meanwhile, in the profit survey, 25% of respondents answered that they had made profits of more than 20 million, while 41.7% of respondents answered that they had made profits of 1 to 5 million. Based on the research results, it is very possible to develop tiger prawn cultivation in the Brebes area.